Связи изменчивости максимальных среднесуточных скоростей ветра над крымским полуостровом, а также изменений потока тепла, доставляемого в Северную Aтлантику водами Южно-Пассатного течения - Аксенова, А.А. (Культура народов Причерноморья, 2013)
Изучены особенности влияния глобального климатического индекса TSA на межгодовую
изменчивость максимальных среднесуточных скоростей ветра на территории Крымского полуострова.
Выявлены районы полуострова, где в те или иные месяцы влияние данного индекса на изучаемую
характеристику ветрового режима в периоды с 1973 по 1994 гг. и с 1989 по 2010 гг. было
статистически значимым.
Ключевые слова: глобальный климатический индекс, максимальная среднесуточная скорость ветра,
корреляция, статистическая связь. Вивчені особливості впливу глобального кліматичного індексу TSA на міжрічну мінливість
максимальних середньодобових швидкостей вітру на території Кримського півострова. Виявлені райони
півострова, де в ті чи інші місяці вплив даного індексу на досліджувану характеристику вітрового
режиму в періоди з 1973 по 1994 рр. і з 1989 по 2010 рр. був статистично значимим.
Ключові слова: глобальний кліматичний індекс, максимальна середньодобова швидкість вітру,
кореляція, статистичний зв'язок. The features of the impact of global climate index TSA on interannual variability of maximal average
daily wind speeds over the Crimean Peninsula are studied. The importance of identifying features of the
influence wind regime characteristics to changes in various natural climatic processes is analyzed. Connection
between time series of interannual changes TSA as well as the maximal average daily wind speed over the
territory of Crimea, the time shift between them 0 to 60 months. Statistically significant areas over the peninsula
where in certain months influence of the studied index on the wind mode in the period from 1973 to 1994 and
from 1989 to 2010 are identified. Proved that impact of global climate change index TSA of average maximal
average daily wind speeds over the territory of the Crimean peninsula from 1973 to 2010 steadily increased.
Reduction of statistical relationships between the studied process in january, march and october are described.
Given the identification of trends suggests that in the near future, most likely further increase the statistical
relationships between the studied processes. Hence record of such relationships in the modelling and forecasting
of meteorological conditions in the Crimea is appropriate.
Keywords: global climate index, maximum average daily speed of wind, correlation, statistical correlation.